0.12(y-7)+0.06y=0.02y-1.8

Simple and best practice solution for 0.12(y-7)+0.06y=0.02y-1.8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.12(y-7)+0.06y=0.02y-1.8 equation:


Simplifying
0.12(y + -7) + 0.06y = 0.02y + -1.8

Reorder the terms:
0.12(-7 + y) + 0.06y = 0.02y + -1.8
(-7 * 0.12 + y * 0.12) + 0.06y = 0.02y + -1.8
(-0.84 + 0.12y) + 0.06y = 0.02y + -1.8

Combine like terms: 0.12y + 0.06y = 0.18y
-0.84 + 0.18y = 0.02y + -1.8

Reorder the terms:
-0.84 + 0.18y = -1.8 + 0.02y

Solving
-0.84 + 0.18y = -1.8 + 0.02y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-0.02y' to each side of the equation.
-0.84 + 0.18y + -0.02y = -1.8 + 0.02y + -0.02y

Combine like terms: 0.18y + -0.02y = 0.16y
-0.84 + 0.16y = -1.8 + 0.02y + -0.02y

Combine like terms: 0.02y + -0.02y = 0.00
-0.84 + 0.16y = -1.8 + 0.00
-0.84 + 0.16y = -1.8

Add '0.84' to each side of the equation.
-0.84 + 0.84 + 0.16y = -1.8 + 0.84

Combine like terms: -0.84 + 0.84 = 0.00
0.00 + 0.16y = -1.8 + 0.84
0.16y = -1.8 + 0.84

Combine like terms: -1.8 + 0.84 = -0.96
0.16y = -0.96

Divide each side by '0.16'.
y = -6

Simplifying
y = -6

See similar equations:

| 4t-3=t+9 | | x+13x+30= | | -(x-1)=-2(-x-1)-4 | | X/6x-1=5 | | 3x^2=3+8x | | X/6x-1=5/1 | | x+11x+28= | | 02.0x+0.35(50)=22.5 | | -172+-8w+4y^2=0 | | 2k-1=k+7 | | x+4/7=x-2/5 | | 17x-13y=7 | | 6+3(x-7)=82 | | 3y+5=13-y | | 7y+3=3y+5 | | 17x+13y=7 | | 5/6x+6/5=-6/5 | | O(10)=2*10-1 | | 495/x=55 | | 2x*3-3-3-3=10 | | (x-2)=4(-4x-5) | | 4(3-x)-3(2-x)=9 | | 4/5x+6/5=-6/5 | | 3x+2/5 | | (3+v)(2v-7)=0 | | 3124/x=344 | | 3124x=344 | | 5x-3+6x+7=4x+7x+1 | | -6x-25=3x+11 | | (3124/495)x=344/55 | | h=-0.5x^2+0.5x+28 | | X^2+-7x+10=0 |

Equations solver categories